Understanding Students’ Perceptions of Doing Mathematics: A Cultural Comparison - Gabriel T Matney; Corrinne Fischer; Jack L Jackson II (SEAMEO Regional Centre for QITEP in Mathematics, 2022)
Garnering different kinds of data from students about their perceptions of mathematics helps teachers, teacher leaders, districts and researchers better understand students’ perceptions. In this study, we investigate and compare students’ perceptions of doing mathematics from samples of students from the United States, China, and Fiji. We administered the Draw Yourself Doing Mathematics instrument to students at three grade levels in China, Fiji, and the United States of America. Statistically significant differences among perceptions in the three countries and the three grade levels were observed. Student drawings were further analysed for other qualitative components including factors affecting the learning environment such as the presence of desks and working with others. Discussion is given about the instrument’s connection to other forms of perceptions research and implications for the use of the instrument by teachers, teacher leaders, and researchers.